(untitled) (The Research of Medical Science Review, 2024)
Cigarette smoking remains a significant public health issue worldwide, with a variety of health consequences impacting both individuals and communities. This study investigates the prevalence of cigarette smoking and its demographic factors in Peshawar, Khyber Pakhtunkhwa, Pakistan, with a particular focus on age, gender, and socioeconomic characteristics. A cross-sectional survey was conducted with 126 participants, including 117 males and 9 females, to examine smoking behaviors and associated health conditions. Data were analyzed using descriptive and inferential statistics, including chi-square tests and logistic regression. The study revealed a high prevalence of smoking among males (92.1%) compared to females (7.9%), with significant variations across different age groups. The 30-40 age group showed the highest prevalence, followed by the 40-50 age group. Health-related issues, such as respiratory problems and premature skin aging, were prevalent among smokers, with gender and age group playing a significant role in the outcomes. These findings underscore the need for targeted public health interventions to reduce tobacco use and address its health impacts, particularly in higher-risk groups.